Pemanfaatan Web Online Single Submission (OSS) Untuk Pembuatan NIB Dalam Meningkatkan Umkm Keluarga Islami di Desa Taro’an - Mohammad Fahrur Rozi; Syaiful Anam; Rini Aristin; Abd. Wahab Syahroni (Jurnal Kabar Masyarakat, 2023)
The activities of the University of Madura Real Work Lecture Program (KKN) in Taro'an Village, Tlanakan District, Pamekasan Regency, East Java Province had a positive impact on the development of MSMEs in Taro'an Village. One aspect that is very important in the development of MSMEs is business legality. Business legality has an important role because the legality of a business is a form of granting permits for organizers of business activities that are granted by the competent authority to business actors. With the Online Single Submission web, it makes it easier for business people to make NIB. In Taro'an Village there are 2 excellent SMEs, namely Kripik Tette and Traditional Jamu such as sinom and betel keys. The purpose of this study is to provide an explanation of the importance of making a Business Identification Number (NIB) as an activity for micro, small and medium enterprises (MSMEs) in Taro'an Village. Community Service Lecture (KKN) activities will help provide understanding to the community and introduce NIB. The method used in this activity is to provide an overview of the Business Identification Number (NIB), to help register the Business Identification Number (NIB) on the OSS website for MSME actors in Taro'an Village in order to obtain a Business Identification Number (NIB), and submit Identification Number Business (NIB) for MSME actors in Taro'an Village